Case report: Systemic sclerosis during neoadjuvant therapy for breast cancer in a 59-year-old woman - Liu, Siyu; Xiao, Xiaomei; Yue, Fangjing; Su, Cong; Tong, Yujun; Xu, Weiyun (Frontiers in Immunology, 2024)
Systemic sclerosis (SSc) is an autoimmune connective tissue disease with skin fibrosis being the first and most common manifestation. Patients with SSc have a higher risk of developing malignant tumors than the general population. However, the sequence and underlying mechanisms linking SSc to malignancy remain controversial. This article presents the case of a 59-year-old woman who was diagnosed with SSc after developing skin fibrosis during neoadjuvant therapy for breast cancer. Despite aggressive antitumor treatments, including targeted therapy, SSc did not improve and progressed rapidly with increasing dermatofibrosis. Remarkably, the SSc entered remission following the cessation of antitumor therapy. Additionally, we reviewed the literature on SSc and malignant tumors, examined their relationship, and discussed key points regarding their identification and potential for adverse drug reactions.